(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
The study aimed to measure and analyze the effect of supply chain in achieving competitive advantage in the Jordanian companies of the human pharmaceutical industry. The population of the study consisted of 6 Jordanian human pharmaceutical companies. The analysis unit consisted of 320 managers in upper and middle management levels (general manager, deputy general manager, assistant manager, department manager). The sample of the study consisted of 250 respondents selected by comprehensive survey method. Descriptive analysisl method was used; a questionnaire was used as a tool to collect the data. The study found statistically significant impact at significance level (α≤0.05) of supply chain with its combined dimensions (suppliers integration, internal intergration, information sharing) in achieving competitive advantage with its combined dimensions (cost, innovation, flexibility, delivery) in human pharmaceutical companies. The study recommended that human pharmaceutical companies should give attention to supply chain methodology to get benefit of its outputs which can contribute to achieve a competitive advantage.